Principles of Bioenergetics - Skulachev, Vladimir P.; Bogachev, Alexander V.; Kasparinsky, Felix O. (Springer Berlin Heidelberg : Imprint: Springer, 2013)
Principles of Bioenergetics summarizes one of the quickly growing branches of modern biochemistry. Bioenergetics concerns energy transductions occurring in living systems and this book pays special attention to molecular mechanisms of these processes. The main subject of the book is the "energy coupling membrane" which refers to inner membranes of intracellular organelles, for example, mitochondria and chloroplasts. Cellular cytoplasmic membranes where respiratory and photosynthetic energy transducers, as well as ion-transporting ATP-synthases (ATPases) are also part of this membrane. Significant attention is paid to the alternative function of mitochondria as generators of reactive oxygen species (ROS) that mediate programmed death of cells (apoptosis and necrosis) and organisms (phenoptosis). The latter process is considered as a key mechanism of aging which may be suppressed by mitochondria-targeted antioxidants.